Exploring The Knowledge, Attitude, And Practice Of Parents Of Under-Five Children with Otitis Media at the Mampong Municipal Hospital, Ghana - opoku, oscar; Owusu Opoku, Abigail; Opoku Agyemang, Cecilia; Yussif , Sumaila; Okudzeto , Henry (Chakra Brahmanda Lentera Institute, 2023)
Background: The study assessed the knowledge, attitude, and practice of parents of under-five children on otitis media using the Mampong Municipal Hospital. Methods: The study used a descriptive qualitative approach. Purposive sampling was used to select 15 participants. The interview guide was employed to gather data and analyze thematically. Results: Parents were aware of otitis media but called in their local dialect with different names. Parents have information about otitis media through the health care centers. Otitis media is caused by children putting things in their ears, playing together, improper bathing of children, swimming, overcrowding, and corporal punishment. It can affect hearing ability, communication, sleeping, appetite, academic performance, and long-term brain damage. Moreover, parents believed that otitis media could be cured. Parents identified health care services as the best way to treat otitis media. Conclusion: The study was limited to only patients of Mampong Municipal Hospital, and the qualitative nature of the research did not permit the generalization of the findings. Explore the management practices of parents on otitis media among children.